INNOVATIONS IN LEGAL MANAGEMENT: TRANSFORMING THE ROLE OF LAW DEPARTMENTS IN ORGANISATIONS - Latif Karim; Sigit Pandu Cahyono; Mohd Syahrin (Adisam Publisher, 2025)
In an era of digital revolution where interconnectivity and globalisation are growing at a rapid pace, innovation in legal management has become a necessity for every organisation to survive in the midst of fierce competition and comply with increasingly complex regulations. Legal departments that used to focus on reactive roles such as dispute resolution and fulfilling minimum obligations are now transforming into more strategic and proactive entities. The implementation of advanced technologies such as artificial intelligence, data analytics and automation has changed the way law departments work, enabling increased efficiency, reduced costs and a focus on value-added activities. Globalisation and increasing regulatory complexity require law departments to have rapid adaptability and a deep understanding of the laws of various jurisdictions. The role of the legal department has expanded from a mere compliance watchdog to a strategic business partner capable of responding responsively to changing regulations and market dynamics. However, this transformation is faced with obstacles such as internal resistance to change, limited resources, and the challenge of integrating new technology into existing systems. The success of legal management innovation depends on effective strategy, visionary leadership, and appropriate investment in human resources and technology. In conclusion, to achieve effective and innovative legal management, an organisation needs to overcome these constraints through a strategic and progressive approach. By creating an enabling environment for innovation and growth, legal can act as a strategic partner that not only ensures compliance and risk management but also supports the sustainable achievement of business objectives.